War and peace - Tolstoy, Leo, graf, 1828-1910 (2018 Great American Read., 2008)
From Pevear and Volokhonsky, the bestselling, award-winning translators of "Anna Karenina" and "The Brothers Karamazov," comes a brilliant, engaging, and eminently readable translation of Tolstoy's master epic.